Closure of an oroantral fistula by bone autograft: a case report - Amroun Samy; Zouari Yassine; Bouattour Ayman (EDP Sciences, 2018)
Introduction: The management of the oroantral fistula is mainly focused on th closure of the mucosa. The surgical management restoring the underlying bone defect are seldom. Maintaining this defect may compromise implant rehabilitation in this sector. The purpose of this article was to show, through a clinical case, an alternative way to manage an oroantral fistula and the bone tissue defect in the same time. Observation: After a rigourous clinical and radiological observation of a 2-year oroantral fistula, an impacted autologous bone graft of the maxillary tuberosity followed by a water tight closure of the mucosa, were realized in a 50-year old patient. Commentary: Using this surgical technique was successful for the closure of the mucosa as for the bone defect reconstruction. A consolidation was noticed and an pre-implant management and a dental implant placement could be realized. Conclusion: The choice of this surgical technique for the management of an oroantral fistua had a direct influence on the future prosthetic rehabilitation. The surgical technique presented for this case could be an interesting approach because the fixed or removable prosthetic treatment will be more effective if the maxillary bone tissue is reconstructed.